Fully automated calcium detection using optical coherence tomography - Athanasiou, Lambros S.; Bourantas, Christos V.; Rigas, George A.; Exarchos, Themis P.; Sakellarios, Antonis I.; Siogkas, Panagiotis K.; Papafaklis, Michail I.; Naka, Katerina K.; Michalis, Lampros K.; Prati, Francesco; Fotiadis, Dimitrios I. (2013 35th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC), 2013)
Optical Coherence Tomography (OCT) is a new invasive technology for performing high-resolution cross-sectional imaging of the coronary arteries. In OCT images only Calcified plaque (CA) components can be accurately depicted as light penetrates hard tissue. In this work we present an automated method for detecting CA in OCT images. The method is fully automated as no user intervention is needed and includes three steps. In the first step the region between the lumen and the maximum penetration depth of OCT from the lumen border is determined. In the second step the region is classified into 3 clusters using the K-means algorithm. CA is identified using the results of k-means. The method was validated using expeerts' annotations on 27 images. The sensitivity of the method is 83% with Positive predictive value (PVV) 74 %.